2012
DOI: 10.1007/s00268-012-1523-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Pain after Open Ventral Hernia Repair by Underlay Mesh Placement

Abstract: Intraperitoneal composite mesh placement after ventral hernia repair is safe with regard to intra-abdominal potential complications. Chronic pain is not uncommon, with chronic cough identified as the major independent predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…Specifically, although trained abstractors are used for reporting clinical outcomes, such as those documented by the physician, the comprehensiveness is limited to the data points evaluated in the IHMR. Possible covariates for poor QOL [38,39], such as chronic cough, alcohol abuse, eventration, and others not listed in our results, were not collected and analyzed in our multivariate model. Although we have excellent follow-up for QOL outcomes at 1 y, as in all such studies, we do not know patient outcomes in those who did not participate in the follow-up.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Specifically, although trained abstractors are used for reporting clinical outcomes, such as those documented by the physician, the comprehensiveness is limited to the data points evaluated in the IHMR. Possible covariates for poor QOL [38,39], such as chronic cough, alcohol abuse, eventration, and others not listed in our results, were not collected and analyzed in our multivariate model. Although we have excellent follow-up for QOL outcomes at 1 y, as in all such studies, we do not know patient outcomes in those who did not participate in the follow-up.…”
Section: Discussionmentioning
confidence: 84%
“…However, when comparing tacks to suture mesh fixation, Nguyen et al [37] reported similar pain scores at 1 wk, 1 mo, and 2 mo in their small prospective comparison in LVHR. Some studies have found preoperative predictors to also be associated with poor postoperative outcomes, like Gronnier et al [38] who found chronic cough to be an independent predictor of chronic pain following VHR with intraperitoneal composite mesh placement. Studies have also found that patients with a history of chronic pain preoperatively have higher odds of chronic abdominal discomfort and decreased functional status following VHR [10,39].…”
Section: Discussionmentioning
confidence: 97%
“…No impact of girdle use on pulmonary function or intra‐abdominal pressure could be demonstrated after midline laparotomy. Some authors recommend the use of a post‐operative girdle even if evidence of benefit is weak, and some recommend a girdle after stoma surgery to avoid the development of a parastomal hernia . There are those who recommend girdle use after repair of diastasis of the rectus muscles, to reduce the risk for recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the results of this study suggest that the EHS width classification is useful for predicting the foreign body feeling and chronic pain after incisional hernia repair. In another prospective study of the authors, primary and incisional hernia were compared in terms of postoperative complications [15]. They found overall complication rates (wound, surgical, and medical) were significantly different (4.4%) for primary hernia versus (15%) incisional hernia (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is one of the complications that can develop after VHR and is an undesirable situation for both patient and surgeons. Though there are many factors increasing recurrence, one of the most commonly blamed factors is DM [16]. Moreover, for DM, a HbA1c >7% has been found to be associated with an increased risk of wound infection [17].…”
Section: Discussionmentioning
confidence: 99%